2015
DOI: 10.1161/jaha.115.002597
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Anticoagulation Use and Cardioembolic Risk After Catheter Ablation for Atrial Fibrillation

Abstract: BackgroundThere is significant practice variation in oral anticoagulation (OAC) use following catheter ablation for atrial fibrillation. It is not clear whether the risk of cardioembolism increases after discontinuation of OAC following catheter ablation.Methods and ResultsWe identified 6886 patients within a large national administrative claims database who underwent catheter ablation for atrial fibrillation between January 1, 2005, and September 30, 2014. We assessed the effect of time off of OAC by CHA 2 DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 34 publications
5
43
0
Order By: Relevance
“…Though this is likely attributed to a decision by the physician or patient to not initiate an OAC, we cannot rule out the possibility that the administrative database did not accurately reflect actual OAC use. These findings, however, correlate with our previous report of high rate of OAC discontinuation of 40% and 60% at 3 and 12 months after AF ablation, which correlated with increased risk of stroke 27. The OLDW contains only privately insured and Medicare Advantage enrollees, so the conclusion may not necessarily be generalizable to Medicaid, Medicare fee‐for‐service, or uninsured populations.…”
Section: Discussionsupporting
confidence: 78%
“…Though this is likely attributed to a decision by the physician or patient to not initiate an OAC, we cannot rule out the possibility that the administrative database did not accurately reflect actual OAC use. These findings, however, correlate with our previous report of high rate of OAC discontinuation of 40% and 60% at 3 and 12 months after AF ablation, which correlated with increased risk of stroke 27. The OLDW contains only privately insured and Medicare Advantage enrollees, so the conclusion may not necessarily be generalizable to Medicaid, Medicare fee‐for‐service, or uninsured populations.…”
Section: Discussionsupporting
confidence: 78%
“…Some of the discontinuation or interruption of anticoagulation might be clinically warranted because of the development of contraindications or need for surgery. Anticoagulation may also be indicated for only a short time after ablation or cardioversion 16, 52. In fact, our recent study that used the same database demonstrated similar treatment heterogeneity in patients undergoing catheter ablation: it may be beneficial for high‐risk patients to continue anticoagulation beyond 3 months after ablation, while low‐risk patients may safely discontinue the medication 52.…”
Section: Discussionmentioning
confidence: 95%
“…Anticoagulation may also be indicated for only a short time after ablation or cardioversion 16, 52. In fact, our recent study that used the same database demonstrated similar treatment heterogeneity in patients undergoing catheter ablation: it may be beneficial for high‐risk patients to continue anticoagulation beyond 3 months after ablation, while low‐risk patients may safely discontinue the medication 52. However, in most cases, the indication for oral anticoagulants is lifelong and time not taking of oral anticoagulants likely reflects a patient's considered decision 53.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in AF have shown benefit in continuing anticoagulation indefinitely in patients having higher CHADS 2 scores. 124 …”
Section: Continuation Of Anticoagulationmentioning
confidence: 99%